2021
DOI: 10.1155/2021/1319090
|View full text |Cite
|
Sign up to set email alerts
|

Associated Factors for Dropout of First Vs Third Doses of Diphtheria Tetanus Pertussis (DPT) Vaccination in Nepal

Abstract: Background. Immunization acts as a key intervention to reduce under-five mortality and morbidity. Despite global progress on vaccination, difficulties in the utilization of this service in developing countries have been observed. According to Nepal Demographic and Health Survey (NDHS) 2016, only 78% of children received a complete dose of vaccine among which the first-dose receiver of DPT is 98%, whereas only 83% received a third dose. This study aims to explore the influencing factors of DPT vaccination dropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
5
5
1
Order By: Relevance
“…Residing in rural areas doubles the risk of vaccination dropout. This finding was in accordance with the findings of other studies conducted in northwest Ethiopia, 15 Nepal, 29 and Shewa Robit. 30 This could be due to the fact that health services are inaccessible in rural areas compared with urban areas.…”
Section: Jama Network Open | Public Healthsupporting
confidence: 93%
“…Residing in rural areas doubles the risk of vaccination dropout. This finding was in accordance with the findings of other studies conducted in northwest Ethiopia, 15 Nepal, 29 and Shewa Robit. 30 This could be due to the fact that health services are inaccessible in rural areas compared with urban areas.…”
Section: Jama Network Open | Public Healthsupporting
confidence: 93%
“…It was found that both can affect the dropout rate. This nding was also con rmed in other studies such as the study done in northwest Ethiopia, Nepal, EDHS 2016 and Shewarobit (18, [22][23][24]. The possible explanation for this might be health facilities in the rural areas can be far for mothers, and it may take time to rehabilitate and reconstruct the health system in the rural areas.…”
Section: Discussionsupporting
confidence: 80%
“…Home delivery increases the risk of drop out of immunization by 75%. This nding is also supported by studies conducted in Nepal and western Ethiopia (11,23). Mothers who give birth at home are likely to have limited communication with health professionals and information about immunization.…”
Section: Discussionmentioning
confidence: 56%
“…Long travel distances to medical facilities, living in a rural region, and having a mother without a regular work were reported to be risk factors for immunization dropout in Nepal. 30 Children in other parts of Ghana were more likely to drop out of school if they lacked immunization records than those who did. 31 Last but not least, a randomized controlled experiment conducted in urban Pakistan found that receiving both a redesigned card and center-based education was expected to significantly enhance DPT3 completion compared to the control group.…”
Section: Introductionmentioning
confidence: 99%